KONSEP PEMASARAN INTI SEBAGAI FONDASI STRATEGI BISNIS BERORIENTASI KONSUMEN - Nur Afifah Lutfina; Firman Firdaus; Acep Rohendi (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2025)
In the era of globalization and digitalization, marketing strategies play a crucial role in ensuring business sustainability and competitiveness. This article aims to examine the core marketing concept as the foundation for developing consumer-oriented business strategies. The research method employed is a literature study by analyzing various studies related to marketing strategies, consumer orientation, competitor orientation, and digitalization. The findings indicate that the core marketing concept is not merely a promotional tool but serves as the basis of business strategy, encompassing segmentation, positioning, and building long-term customer relationships. Both consumer and competitor orientation positively influence marketing performance, while digital and sustainability strategies enhance customer loyalty and corporate image. Furthermore, customer satisfaction is found to be more strongly influenced by product quality and location than by price and promotion. Therefore, implementing the core marketing concept with a consumer-centered approach, responsiveness to competitor dynamics, and adaptability to digital technology is essential for achieving business success in today’s global competition